Coma and Disorders of Consciousness (Springer International Publishing, 2018)
This revised and expanded second edition discusses the assessment and treatment of patients recovering from coma and disorders of consciousness. Besides diagnostic, prognostic and ethical issues, this book describes well-established techniques and procedures, and also techniques under development. New chapters include consciousness theories, issues relating to long-term care, and neuromodulation treatments. Coma and Disorders of Consciousness, Second Edition is a comprehensive review of the field for clinicians and researchers, regardless of whether they are already familiar with the difficult but exciting field of disorders of consciousness.